RELAÇÕES ENTRE CARACTERÍSTICAS DOS INTEGRANTES DE EQUIPES, COMPETÊNCIAS COLETIVAS E DESEMPENHO COLETIVO - Giansante, Cláudia Cintra Bortoletto (2013)
Technological innovations and changes in the form of work have become fundamental parts in performance teams of organizations and individual improvement. Theoretical research identifies that the knowledge of the characteristics of the team and its members provides performance, organizational development, social interactions and how they will be performed the tasks. The study by investigative question analyse the relations of characteristics of the members of the teams that include socio-demographic characteristics, individual skills, psychological types, with the collective skills and collective performance. The search context is a technology course in gastronomy at a private University, a sample of 131 students, ten teams of fourth semester and eleven of the second semester in practical activities in the laboratory of food. It is a descriptive research that employs the correlation method for quantitative data, as individual and collective skills and academic performance collective notes, besides qualitative interpretations by observation in twelve meetings of the teams for collective work and a quality-quantitative analysis of data. The study highlights the absence of correlation between the variables in the teams of 2nd semester justified for being quite young teams and in initial academic and professional development phase. On the team of 4th semester, the Pearson coefficient indicates significant correlation and proves that the characteristics of a positive influence on the collective skills and result in better performances collectives. Qualitatively, the best teams are managed by a lead female adult who coordinates the tasks and the members are contributors and employees, while the leader is communicator and challenger. Develop a dynamic work pace with strong presence of communication, quick and creative decision-making and reach differentiated targets in gastronomy. Although the results cannot be generalized because the research has been carried out in only one University and involving 21 teams, the theoretical concepts are and can be tested in other realities.